Population-Based Assessment of the Long-Term Risk of Seizures in Survivors of Stroke - Alexander E. Merkler; Gino Gialdini; Michael P. Lerario; Neal S. Parikh; Nicholas A. Morris; Benjamin Kummer; Lauren Dunn; Michael Reznik; Santosh B. Murthy; Babak B. Navi; Zachary M. Grinspan; Costantino Iadecola; et al. (2018)
Background and Purpose— We sought to determine the long-term risk of seizures after stroke according to age, sex, race, and stroke subtype. Methods— We performed a retrospective cohort study using administrative claims from 2 complementary patient data sets. First, we analyzed data from all emergency department visits and hospitalizations in California, Florida, and New York from 2005 to 2013. Second, we evaluated inpatient and outpatient claims from a nationally representative 5% random sample of Medicare beneficiaries. Our cohort consisted of all adults at the time of acute stroke hospitalization without a prior history of seizures. Our outcome was seizure occurring after hospital discharge for stroke. Poisson regression and demographic data were used to calculate age-, sex-, and race-standardized incidence rate ratios (IRR). Results— Among 777 276 patients in the multistate cohort, the annual incidence of seizures was 1.68% (95% confidence interval [CI], 1.67%–1.70%) after stroke versus 0.15% (95% CI, 0.15%–0.15%) among the general population (IRR, 7.3; 95% CI, 7.3–7.4). By 8 years, the cumulative rate of any emergency department visit or hospitalization for seizure was 9.27% (95% CI, 9.16%–9.38%) after stroke versus 1.21% (95% CI, 1.21%–1.22%) in the general population. Stroke was more strongly associated with a subsequent seizure among patients <65 years of age (IRR, 12.0; 95% CI, 11.9–12.2) than in patients ≥65 years of age (IRR, 5.5; 95% CI, 5.4–5.5) and in the multistate analysis, the association between stroke and seizure was stronger among nonwhite patients (IRR, 11.0; 95% CI, 10.8–11.2) than among white patients (IRR, 7.3; 95% CI, 7.2–7.4). Risks were especially elevated after intracerebral hemorrhage (IRR, 13.3; 95% CI, 13.0–13.6) and subarachnoid hemorrhage (IRR, 13.2; 95% CI, 12.8–13.7). Our study of Medicare beneficiaries confirmed these findings. Conclusions— Almost 10% of patients with stroke will develop seizures within a decade. Hemorrhagic stroke, nonwhite race, and younger age seem to confer the greatest risk of developing seizures.